Inside IB and RAW : The Rolling Stone that Gathered Moss - Sankaran Nair, K. (Kinattinkara), 1920- (New Delhi, India Manas Publications, 2008)
Autobiographical memoirs of a former head of Indian intelligence.
Includes Index.
Keywords: India -- Intelligence Officers